Tree-ring reconstruction of forest disturbances: evaluation of methods and past changes on forest dynamic - Altman, Jan (Jihočeská univerzita, 2014)
Tree-ring data serves as a chronicle of the past environment and provides long-term records about climate variations, volcanic eruptions, glacial activity and many others processes. Over the past few decades, dendrochronology has become common in studying disturbances. This thesis is focused on release detection methods (i.e. abrupt growth after death of neighbouring tree(s)) and their application. The presented review showed that despite the some uncertainties in methodological approaches, release detection is a reliable tool for forest disturbance reconstruction. In this thesis, release detection was applied in various forest ecosystems for reconstruction of disturbances and their effects. The achieved results importantly contribute to the understanding of the ecological processes concerning forest management, long-term changes in natural forest ecosystems, forest diversity and the impact of global changes.
Tree-ring reconstruction of forest disturbances: evaluation of methods and past changes on forest dynamic
Keywords: tree-ring; forest disturbance; methods; growth-change; forest dynamic; regeneration; tree-ring; forest disturbance; methods; growth-change; forest dynamic; regeneration